PRACTICAL ASPECTS OF THE APPLICATION OF BACTERIAL STARTER CULTURE IN THE PRODUCTION OF SOUR-CREAM BUTTER OBTAINED ON A CONTINUOUS BUTTER MAKING MACHINES - Y. V. Lapshenkova; N. Y. Dykalo; M. I. Shramko; M. I. Slozhenkina; I. A. Evdokimov (Современная наука и инновации)
The strategy for the development of the food industry is the basis for the formation of a national food quality management system.